2020
DOI: 10.1186/s12915-020-00914-0
|View full text |Cite
|
Sign up to set email alerts
|

System-wide molecular dynamics of endothelial dysfunction in Gram-negative sepsis

Abstract: Background Inflammation affecting whole organism vascular networks plays a central role in the progression and establishment of several human diseases, including Gram-negative sepsis. Although the molecular mechanisms that control inflammation of specific vascular beds have been partially defined, knowledge lacks on the impact of these on the molecular dynamics of whole organism vascular beds. In this study, we have generated an in vivo model by coupling administration of lipopolysaccharide wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…None of these studies report KEGG pathways and/or GO hits that are downregulated. Consistent with genomic studies, proteins expressed correlate with the upregulation of KEGG pathways and GO hits related to coagulation, cell adhesion and immune response (56,57,58,59,60,61,62). Thus, proteins correspond with gene expression to determine final cellular pathways and biological processes overexpressed in septic-like conditions.…”
Section: Proteomics Of Mouse Ecssupporting
confidence: 56%
See 2 more Smart Citations
“…None of these studies report KEGG pathways and/or GO hits that are downregulated. Consistent with genomic studies, proteins expressed correlate with the upregulation of KEGG pathways and GO hits related to coagulation, cell adhesion and immune response (56,57,58,59,60,61,62). Thus, proteins correspond with gene expression to determine final cellular pathways and biological processes overexpressed in septic-like conditions.…”
Section: Proteomics Of Mouse Ecssupporting
confidence: 56%
“…Other than causing differential regulation of coagulation, cell adhesion and immune response proteins in ECs, sepsis has been shown to affect the glycocalyx (a gel-like layer composed of proteoglycans coating ECs) and vascular smooth muscle cells (VSMCs) (7,58). The synthesis of new peptides in response to sepsis related to lipid transport (e.g.…”
Section: Proteomics Of Mouse Ecsmentioning
confidence: 99%
See 1 more Smart Citation
“…For protein identification precursor mass tolerance was set at 10 ppm and a reporter ion integrated tolerance at 20 ppm. Label-free quantification of proteins was based on spectral count as previously reported [ 16 ]. The most abundant proteins identified (spectral count > 20) were included in the performed analyses as indicated in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been demonstrated that administration in mice of P. gingivalis , one of the main pathogenic bacteria present in periodontitis, increases intestinal permeability and, as a consequence, facilitates the transfer of LPS through the intestinal barrier [ 48 , 128 ]. This leakage of LPS leads to upregulated serum LPS levels, which in turn have been demonstrated to trigger systemic inflammation [ 48 , 128 , 129 ]. Repeated oral application of P. gingivalis induces neurodegeneration and the formation of extracellular Aβ42 in young adult wild type mice, strongly suggesting that low grade chronic periodontal infection with this pathogen can result in the development of neuropathology consistent with that of AD [ 130 ].…”
Section: Resultsmentioning
confidence: 99%